Editorial. (1st January 2012) - Nepal, Surya; Pathan, Mukaddim
Cloud computing has emerged as a new paradigm for the on-demand delivery of computing services to consumers as utilities. Given its innovative nature compared to the standard model of service provisioning, cloud computing raises new questions in terms of security, privacy and trust. Therefore, our focus in this special issue is to analyse the security, privacy and trust aspects of cloud with the aim of providing trusted cloud systems. In this editorial, we first provide a brief overview on various aspects of security, privacy and trust in cloud systems and discuss related recent research and development activities. We then present a brief summary of each of the papers included in this special issue.